Perancangan Sistem Informasi Geografis Wisata Halal Provinsi Sumatera Barat Berbasis Mobile - nori sahrun (JUSS (Jurnal Sains dan Sistem Informasi), 2022)
The World Halal Tourism Award has designated West Sumatra Province as a halal tourism destination. As a halal tourism destination, West Sumatra Province needs to improve itself to fulfill the wishes of tourists in traveling. One of the supports for halal tourism needs is the existence of a halal tour package that can make it easier for tourists to see routes and information from tourist attractions, restaurants, mosques, or places to sell souvenirs to be visited. In addition, travel agents in West Sumatra Province can develop. Therefore, it is necessary to develop a geographic information system application for halal tour packages to support halal tourism and as a medium for travel agents in making halal tour packages. The development of this application consists of several stages, namely data collection, application development using the waterfall method, and testing the system using the blackbox method. This application is implemented using the programming languages ​​PHP, B4A, and Javascript. The database used to store data is PostgreSQL with the PostGIS extension. The PostGIS functions used are ST_GeomFromText, ST_X, ST_Y, and ST_Centroid. This application can be used to view, search, and find out information on halal tour packages and make it easier for tourists to see halal tour package routes in West Sumatra Province. From the test results with the blackbox method, this application is in accordance with the functional system.